2022
DOI: 10.1002/jbt.23292
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of male reproductive system to bisphenol A, an endocrine disruptor: Updates from epidemiological and experimental evidence

Abstract: Bisphenol A (BPA) is an omnipresent environmental pollutant. Despite being restrictions in‐force for its utilization, it is widely being used in the production of polycarbonate plastics and epoxy resins. Direct, low‐dose, and long‐term exposure to BPA is expected when they are used in the packaging of food products and are used as containers for food consumption. Occupationally, workers are typically exposed to BPA at higher levels and for longer periods during the manufacturing process. BPA is a known endocri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…As a typical environmental endocrine disruptor, BPA at a high dose is unanimously recognized to induce male reproductive toxicity in rodents and humans [ 60 , 61 ]. However, it remains controversial as to whether BPA at a low dose is toxic to the male reproductive system, and a general consensus cannot be reached.…”
Section: Discussionmentioning
confidence: 99%
“…As a typical environmental endocrine disruptor, BPA at a high dose is unanimously recognized to induce male reproductive toxicity in rodents and humans [ 60 , 61 ]. However, it remains controversial as to whether BPA at a low dose is toxic to the male reproductive system, and a general consensus cannot be reached.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that BPA has endocrine-disrupting properties and that it can be implied in the pathogenesis of a variety of human diseases mostly affecting reproductive systems [2,3], similar to other environmental pollutants [4], as well as cardiovascular systems [5]. In this frame, epidemiological studies reported that there is an association between exposure to BPA and an increased prevalence of cardiovascular diseases (CVDs), including atherosclerosis [6], coronary and peripheral artery disease [7,8], myocardial infarction [9], and angina pectoris [10], as well as their risk factors, such as hypertension [11] and diabetes [12].…”
Section: Introductionmentioning
confidence: 99%